Arctic-Alpine plants in Bulgarian mountains - Apostolova, Iva Ivanova; Pedashenko, Hristo; Sopotlieva, Desislava; Velev, Nikolay; Vassilev, Kiril; Meshinev, Tenyo (Lazaroa, 2013)
Bulgarian mountains are the southern distribution limit of several arctic-alpine species in Europe, many of them listed as threatened in the country. We assessed the diversity of arctic-alpine species in different mountain areas and selected the mountains with highest concentration of arctic-alpine species for field survey, sampling a total of 219 plots. The most frequently occurring species are Juncus trifidus, Poa alpina, Dryas octopetala, Bistorta vivipara, Omalotheca supina and Antennaria dioica. The frequency of these species increases with altitude and at northern aspect. Arctic-alpine plants take part in different vegetation classes, but are represented more frequently in Thlaspietea rotundifolii. The species tend to grow together, as a possible result of common functional characteristics and unified survival strategy. In 65% of sampled locations more than one target species were observed. Dianthus microlepis and Primula minima demonstrate very high association with the arctic-alpine species.